Islamic Social Sciences Methodology: An Integrated Framework - Ahmed, Habib (Dirasat: Human and Social Sciences, 2026)
Objectives: The paper aims to develop an integrated methodological framework for Islamic social sciences by combining elements from Islamic methodologies and legacies with Western theoretical concepts and empirical methods to produce beneficial knowledge. Methods: The paper is a conceptual research that builds an Islamic social science methodology by integrating the methodological concepts and methods from both Islamic discourses and Western scientific approaches. After presenting the foundational principles based on the existing literature, the paper develops a five-phase integrated methodological framework for Islamic social sciences. Results: The Islamic social science methodological framework constitutes five phases. First, idea generation and selection of research topic. Second, developing a normative theory by using the values and principles of Sharia, heritage and relevant concepts from Western theoretical constructs. Third, the theoretical inferences are tested against the practice using qualitative, quantitative and mixed scientific methods of collecting and analysing data and information. Fourth, identifying the gaps between theory and practice. Finally, using an iterative process to reduce the divergences by reframing the theoretical constructs and/or changing the practices by applying suitable policies. Conclusions: The knowledge produced by Islamic social science methodology should be beneficial to help build moral societies and enhance human welfare. The integrated methodology uses revelation and reason to carry out normative and positive analyses iteratively to produce beneficial Islamic social science knowledge. Knowledge creation must also be a dynamic ‘becoming process’ and evolve as the social realities, structures, and problems change over time.